2021
DOI: 10.1164/rccm.202009-3386le
|View full text |Cite
|
Sign up to set email alerts
|

Viral Dynamics of SARS-CoV-2 in Critically Ill Allogeneic Hematopoietic Stem Cell Transplant Recipients and Immunocompetent Patients with COVID-19

Abstract: Conclusion: To our knowledge this is the first comprehensive report on COVID-19 in HSCT patients focussing on virological parameters. Compared to immunocompetent patients, prolonged shedding of infectious virus, viremia and high viral loads in respiratory samples, highlights the need of the immune system for viral control, but also indicates virus induced mortality and higher risk for transmission to other patients and medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Severe COVID-19 and the need for mechanical ventilation were higher in allo-HCT recipients compared with auto-HCT recipients, similar to the findings of Verma et al [13] . The mortality rate in 11 patients admitted to the ICU was 73%, consistent with a previous report of 83% mortality in 6 HCT recipients admitted to the ICU [30] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Severe COVID-19 and the need for mechanical ventilation were higher in allo-HCT recipients compared with auto-HCT recipients, similar to the findings of Verma et al [13] . The mortality rate in 11 patients admitted to the ICU was 73%, consistent with a previous report of 83% mortality in 6 HCT recipients admitted to the ICU [30] .…”
Section: Discussionsupporting
confidence: 90%
“…We report a significantly higher mortality of 16% with COVID-19 in HCT/CAR-T therapy recipients compared with the observed case fatality ratio of 1.8% in the general US population [26] . Previous studies have reported a COVID-19-related mortality rate of approximately 20% in HCT/CAR-T therapy recipients [ 13 , 20 , 21 , 22 , 27 , 28 , 29 , 30 ]. In a US cohort of 34 HCT recipients, Verma et al [13] reported 21% mortality from COVID-19, with most of the deaths in the allo-HCT group (25%), which is comparable to the 28% mortality rate of allo-HCT recipients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for severe and fatal courses of COVID-19 is particularly high after allogeneic hematopoietic stem cell transplantation (alloSCT) [1][2][3][4]. Cardiovascular and renal morbidity is increased post COVID-19 [5].…”
Section: To the Editormentioning
confidence: 99%
“…14 We believe that HSCT patients would certainly benefit if we could find a viral-specific quantitative prognostic parameter that can predict the COVID-19 disease course at the earliest in these immunocompromised patients. In a similar attempt, Roedl et al 15 published a case series of six patients with HSCT or chimeric antigen receptor T-cell therapy who required intensive care unit (ICU) level of care for COVID-19 pneumonia. 15 Unlike the reports by Pujadas et al 11 and Magleby et al, 14 they did not find any correlation to suggest that a high respiratory viral load at admission could correlate with high mortality.…”
Section: Available Literaturementioning
confidence: 99%
“…In a similar attempt, Roedl et al 15 published a case series of six patients with HSCT or chimeric antigen receptor T-cell therapy who required intensive care unit (ICU) level of care for COVID-19 pneumonia. 15 Unlike the reports by Pujadas et al 11 and Magleby et al, 14 they did not find any correlation to suggest that a high respiratory viral load at admission could correlate with high mortality. However, they did find a significant viremia in most of their critically ill patients.…”
Section: Available Literaturementioning
confidence: 99%